Associação do índice de pulsatilidade ao exame Dopplerfluxométrico das artérias pulmonares fetais na predição de Hipoplasia Pulmonar - Alim Alves Demian (2002)
Introduction: Pulmonary hypoplasia (PH) is one of the main causes of perinatal morbidityletalidy; several causes are involved in their genesis from the premature rupture of membranes oligohydramnios by until birth congenital membranes both own respiratory and other systemsthat influence in the growth and maturing of the lungs. Your prediction by various methods present conflicting results and assessing fetal pulmonary arteries wave forms study if presented as a promising this tracking method. Objectives: to assess the capacity of the pulsatilidadeindex in examination fetal flow lung arteries in predicting the pulmonary hypoplasia in concepts with risk factors for developing the disease. Patients and methods: were tracked in Fetal Medicine Center (CEMFE) HC/UFMG, 61 patients with risk their foetuses make PH, in June 2000 to April 2002, of 55 patients were included in the study, the gestational age varied between 23 and 39 weeks, confirmed by the date of the last menstruation and medical ultrasonography below the 20th week. The pulmonary arteries wave forms study was done by the same observer and its results were allocated on the curve proposal by Yoshimura in 1999, being concerned with the development of disease risk when the pulsatily index values of both were pulmonary arteries below-2SD curve area. The Association test Chi square test on 2 x 2 tables in various groups and the general assessment. When necessary we use Fisher testing. Results: of 55 foetuses evaluated 45 have changed; examination of these 36 born with pulmonary hypoplasia. When studied together the various causes of HP submitted statistical significance (p0,00001). The risk groups (renal fetal disease, bone diseases, lung diseases,diaphragmatic hernia, hydrops not immune) and high sensitivity of the method, however without statistical significance. Conclusions: examination doppler ultrasound lung arteries presents the possibility of detecting lung hypoplasia frame with reasonable statistical value hasthe power of prediction pulmonary